Effects of changes in fuel volume on the explosion-proof distance and the multiparameter attenuation characteristics of methane-air explosions in a semi-confined pipe. (January 2016) - Jiang, Bingyou; Su, Mingqing; Liu, Zegong; Cai, Feng; Yuan, Shujie; Shi, Shulei; Lin, Baiquan
Abstract: After establishing a semi-confined pipe model with a length of 100 m and a cross-sectional area of 0.08 m × 0.08 m, the multiparameter attenuation characteristics of gas explosions were revealed for fuel volumes of 0.0128 m 3, 0.0384 m 3, 0.064 m 3, and 0.0896 m 3 . The results showed that the maximum overpressure presented a changing trend of decreasing, increasing and decreasing with increasing distance away from the ignition source. The peak overpressure formed by the shock wave, the flame propagation speed, the maximum density, gas velocity, and combustion rate all followed a trend of increasing and decreasing. However, the peak overpressure formed by the sonic compression wave and the maximum temperature decreased gradually as the distance increased. The fuel volume had a distinct effect on the overpressure, density, temperature, gas velocity, and combustion rate of gas explosions. The maximum overpressure, density, temperature, gas velocity, and combustion rate among all of the gauge points increased as the fuel volume increased, and they were almost all linear functions of the fuel volume. The explosion-proof safety distance tended to increase with increasing fuel volume, while the flameproof distance increased linearly. These results can provide theoretical guidance for the disaster relief efforts of the gas explosion in the process industry. Highlights: Multiparameter attenuation characteristics of gas explosions were revealed. Fuel volume had a distinct effect on gas explosion parameters. Increasing fuel volume increased the explosion overpressure. Increasing fuel volume increased the explosion-proof safety distance. Increasing fuel volume increased the flameproof distance linearly.